Observing Online News Portals Activities and Responsibilities During Covid-19 (Global Journal of Human-Social Science, 2022)
This study observes the significant roles and responsibilities of online news portals during this Covid-19 outbreak in Bangladesh The findings and result analysis of this study manifest the tasks along with the activities which online news portals pose specifically in a pandemic situation are on the satisfactory level Through the use of two theories and a quantitative approach this study attempted to distinguish how people think of these portals as a potential media in creating awareness People seem to prefer online news portals more than other media for getting covid-19 related news which lead them to believe and depend on what these portals offer actually On the other hand sometimes these online news portals also teem with some fear regarding moral panic misinformation and rumors even sometimes news with full of confusing repetitive with inadequate reporting languages Despite having all confusion respondents of this study think online news portals have played a responsible role to keep the mass people updated during the Covid-19 situation especially in that situation where the whole world was facing an emergency lock down
Keywords: pandemic; covid-19; social media; trustworthy; awareness; lock down